The comedy of errors - "Shakespeare, William" (sweet cherry publishing: China, 2013)
The Comedy of Errors is one of the earliest plays of the great playwright, William Shakespeare. It revolves around two sets of identical twins who were separated at birth. Years later, fate brings them to the same city, and this unleashes the drama caused by mistaken identities. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play
Keywords: Adaptations Juvenile literature